Differences Between Multicomponent Exercise and Concurrent Exercise on Reducing Frailty Risk in The Elderly in Karangasem - Tri Juniari, Ni Komang; Luh Putu Ratna Sundari; Nur Basuki; I Made Muliarta; I Dewa Ayu Inten Dwi Primayanti; I Made Krisna Dinata (International Journal of Public Health Excellence (IJPHE), 2025)
The worldwide population of older adults is growing, which may yield a demographic bonus; yet, this growth simultaneously heightens frailty risk among the elderly. The dynamic and reversible nature of frailty provides opportunities and challenges in overcoming the aging process. Multicomponent exercise and concurrent exercise are two prominent forms of exercise in elderly exercise programs to reduce frailty risk. This research was to prove the difference in the effect of multicomponent exercise and concurrent exercise on reducing frailty risk in the elderly in Karangasem. Pre and post-test two group methods were used in this study’s true experimental design. Twenty-two participants were chosen by a simple random sample technique and subsequently divided into two groups: the multicomponent exercise group (n = 11) and the concurrent exercise group (n = 11). The exercises were given 3 times for 8 weeks. Frailty risk was assessed based on the Fried's Frailty Phenotype criteria. The Paired Sample T-test results indicated a significant difference in frailty risk reduction before and after exercise in both the multicomponent exercise group (p = 0.001; p < 0.05) and the concurrent exercise group (p = 0.001; p < 0.05). The Independent Samples T-test results indicated no significant difference in frailty risk reduction between the multicomponent exercise group and the concurrent exercise group (p = 0.318; p > 0.05). Based on the study’s findings, multicomponent exercise and concurrent exercise are equally good in reducing frailty risk in the elderly in Karangasem.